When Should Harvest Evolution Matter to Population Dynamics?. (July 2016) - Nusslé, Sébastien; Hendry, Andrew P.; Carlson, Stephanie M.
Abstract : The potential for evolution to influence fishery sustainability remains a controversial topic. We highlight new modeling research from Dunlop et al. that explores when and how fisheries-induced evolution matters for population dynamics, while also emphasizing transient dynamics in population growth and life history-dependent responses that influence population stability and resiliency.